Effect of Web Causation Epidemiological Model on Preventive Behaviors of Diabetic Females with Genitourinary Tract Infection - Shaimaa A. E. Hemida; Seham G. Ragheb; Hemat A. El Sayied; Hala M. Mohamed (Evidence-Based Nursing Research)
Context: Genitourinary tract infection becomes a silent epidemic that devastated female life. It is closely interrelated with hyperglycemia, diabetes, and lack of awareness about personal hygiene care. All increase the susceptibility to various types of infections.